Muscle-bone interaction and vibration
About the NEMES BOSCO SYSTEM AND NEUROMUSCULAR MECHANICAL STIMULATION. The article is about the muscle-bone interaction and vibration. Basic studies of the effects of vibrations at biological level are mentioned as well as studies of vibrations applied to sport and fitness perfromances. Other point are studies of vibrations in rehabilitation and muscle atrophy or in ageing and osteoporosis.